Fratture dell’omero distale: trattamento con protesi di gomito - Ritali, A.; Guerra, E.; Ricciarelli, M.; Zaccaro, R.; Rotini, R. (Lo Scalpello - Journal, 2019)
ELBOW REPLACEMENT FOR DISTAL HUMERAL FRACTURES The treatment of distal humeral fractures could be challenging, especially in the older population. Although some fractures of the distal humerus in the elderly can be managed non-operatively, generally they results in poor outcome, secondary stiffness or nonunion. In young people and in patients with good bone quality, open reduction and stable internal fixation are mandatory, but in patients over 65 y-o, elbow prosthesis could be a good option for treatment. If the patient presents a complex pattern including fracture, osteoporosis, or joint damage from rheumatoid arthritis, total elbow replacement needs to be considered. By contrast, in case of more active patients distal humeral hemiarthroplasty is the ideal choice, being less invasive, with many advantages such as lower patient morbidity, less concerns regarding polyethylene wear, and bone stock preservation for future reconstructive procedures. In this study we reviewed 49 patients, with a mean age of 78. 4 year, who had been treated in our Unit between 2001–2016 for distal humeral fractures. All patients underwent joint replacement (either total elbow arthroplasty or distal humeral hemiartoplasty). The aim of this study was to assess the outcomes in patients treated with elbow replacement at medium-term follow-up and, consequently, to define an algorithm for the treatment of distal humeral fractures in elderly.